FORENSIC ODONTOLOGY – A TECHNOLOGY DRIVEN APPROACH IN HUMAN IDENTIFICATION (Journal of Forensic Medicine & Toxicology, 2022)
Human identification is a major element in forensic investigation with legal, ethical, social, and moral ramifications. Forensic odontology is an integrated specialty that involves identification beyond recognition using oral and para-oral structures such as teeth, jaw bone, saliva, the presence of foreign bodies, skull structures etc1. In circumstances of single corpse identification or mass casualties, this specialty is critical and vital in human identification. Since teeth are frequently resistant to decomposition, they can be used as a tool for forensic identification even in cases of deteriorated and charred bodies. Dr. Oscar Amoedo, known as the “Father of Forensic Odontology,” described the first example and role of dental identification in 1897, when 126 persons were burnt to death in a fire in Paris2.
Keywords: Human; circumstances; structures; Odontology